Arquitetura da informação para biblioteca digital personalizável - Camargo, Liriane Soares de Araújo de [UNESP] (2004)
The recovery and dissemination of unstructured information of the Web environment are difficulties existing nowadays. Some resources which can minimize these difficulties are as digital libraries, which can have simultaneous and remote access to information in an efficient way, as personalization services, which provide a user personalized interaction based on its profile. The problem in providing such resources is the difficulty in developing digital libraries because of the number of elements and processes involved in its building. In this context, is proposed a information architecture for customizable digital libraries, which aims deals with the following problems: lack of specialized literature on information architectures for digital libraries; lack of technological elements and elements of information which allow a fast and accurate access to required information; and the lack of personalization services of content and interface for different kinds of users. This architecture is composed by processes and elements, from Information Science and Computer Science fields, that are share by most of digital libraries. Besides, this architecture contains generic elements, which allow flexibility to be adapted and modified according to the characteristics of each digital library. The aim of the proposed architecture is to help the developer in building Web sites and customizable digital libraries as well. To supplement the project, it was performed an evaluation of the processes and elements more used and common in this type of information unit, in this case: digital libraries. The results of this evaluation showed that the majority of the elements are used by digital libraries and are relevant to its build. This study is a descriptive research with theoretical and methodological approach of the Information Science field, performed by means of a study of bibliographical data... (Complete abstract, access undermentioned eletronic address)